Preparation of an ion imprinted functionalized mesoporous silica for rapid and specific absorption Cr(iii) ions in effluents. Issue 60 (1st August 2017) - Cen, Shuibin; Li, Weiming; He, Rong; Tan, Jiean; Wang, Haishui; Wei, Chaohai; Tang, Youwen
Abstract : We developed an effective and selective method to remove Cr(iii ) ions in acidic effluents. Abstract : We developed an effective and selective method to remove Cr(iii ) ions in acidic effluents. This method used combined ion imprinted technology with mesoporous silica materials. Cr(iii ) ion imprinted mesoporous silica (CrIMS) was synthesized and used as an excellent adsorbent. Iminodiacetic acid (IDA) was silanized, and acted as a functional monomer. The chemical groups, thermal stability, porosity and highly ordered morphology of CrIMS were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), Brunauer–Emmett–Teller (BET) isotherms, X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The Brunauer–Emmett–Teller (BET) surface area was 856.24 m 2 g −1 . The saturated adsorption capacity of CrIMS towards Cr(iii ) ions reached up to 63 mg g −1 at pH 4.5. At a concentration of 200 mg L −1, the adsorption of Cr(iii ) ions reached equilibrium within 5 min and 20 min at pH 4.5 and pH 3.0, respectively. The CrIMS showed highly specific adsorption capacity and the imprinting factor was up to 4.03 at pH 3.0. The adsorption capacity of Cr(iii ) ions was remarkably higher than other co-existing metal ions. After eight adsorption–regeneration cycles, the adsorption efficiency of CrIMS still reached above 94.1%. The CrIMS could effectively remove Cr(iii ) ions below the discharge standard of China in real sample treatment.